Importance of animal husbandry and production management on food safety in livestock production systems - Gauly, Matthias (Acta Biologica Szegediensis, 2006)
Production and management systems do significantly effect animal health and therewith the use of drugs and prophylactic treatments. This may lead to residues and a change for the worse in food safety. The consequent implementation and use of hygiene and management tools and measures is needed, as well as a combination of these measures with effective programmes (e.g. vaccination, procedure with cleaning and disinfection, all in all out etc.) in order to limit the use of drugs in sick animals so they are used only when absolutely necessary. A better education among producers is also an important step towards higher food safety on farm level.